PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA MURID KELAS II UPT SD 94 BEBA - Alfina Damayanti; abdul hurair; Sulvahrul Amin (STKIP Subang, 2025)
This research was designed to evaluate the impact of the implementation of a game-based learning model or Game Based Learning (GBL) on improving the mathematics academic achievement of second-grade students at UPT SD 94 BEBA, Takalar Regency. The decline in mathematics academic achievement at the elementary level is often associated with traditional teaching methodologies that tend to focus on educators. The investigation was conducted using a quantitative methodology and a quasi-experimental design using a One Group Pretest-Posttest design. Data collection was carried out through learning outcome assessments, then analyzed using a paired t-test and N-Gain calculation to measure the effectiveness of score improvement. The analysis findings showed a significant deviation between the pretest and posttest scores, evidenced by a t-statistic value of 15.433 and a significance level of 6.606e-15. The average learning outcome score increased from 79.96 to 83.04 after the implementation of GBL, with an N-Gain index of 0.17 which is categorized as low. This finding indicates that although the increase is statistically significant, the effectiveness of improving learning outcomes is still limited. Overall, the implementation of GBL has been proven to be able to encourage students' motivation, active participation, and understanding of mathematical concepts through enjoyable and student-centered learning experiences.